Re:Research. - Muratovski, Gjoko; Vogel, Craig M. (Intellect Books, 2019)
Just as the term design has been going through change, growth and expansion of meaning, and interpretation in practice and education - the same can be said for design research. The traditional boundaries of design are dissolving and connections are being established with other fields at an exponential rate. Based on the proceedings from the IASDR 2017 Conference, Re:Research is an edited collection that showcases a curated selection of 83 papers - just over half of the works presented at the conference. With topics ranging from the introduction of design in the primary education sector to desi.